PROJECT-BASED LEARNING IN PROMOTING LEARNER AUTONOMY IN AN EFL CLASSROOM - Yuliani, Yuyun; Lengkanawati, Nenden Sri (Universitas Pendidikan Indonesia, 2017)
In the Indonesian context, learning activities tend to be teacher-centered that a teacher still plays a dominant role in the learning process. Project-based learning is one of the approaches which is assumed to promote Learner autonomy. Since its implementation has not been effective, this study is aimed at Â investigating the current issue of how Project-based learning promotes Learner autonomy in an EFL Classroom. It employs descriptive qualitative research design at six participants of Junior High School students, grade nine. The qualitative data collected through document analysis, observation and interview were analyzed qualitatively. The results of data analysis led to a conclusion that project-based learning has promoted Learner autonomy, which covers the criteria of self-instruction, self-direction, self-access learning and individualized instruction in each stage of Project-based Activity, namely the planning process, the implementation process and the monitoring process. There are also six important findings. Firstly, the learner autonomy varies among learners. Secondly, there is a linear relationship between learnersâ€™ achievement and Learner autonomy. Thirdly, Learner autonomy needs process, and the process shows irregular pattern. Fourthly, it is worthy noted that no one is one hundred percent autonomy. Fifthly, among the three stages of the Project-based Activity, the learners gain the highest degree of Learner autonomy in the Implementation Process. Sixthly, there are still constraints in enhancing Learner autonomy. Due to the constraints above, this study recommends that promoting Learner autonomy needs support in some specific areas, especially the professional treatment of the teachers and institutions.